Factors Influencing Investment Decisions of Nepalese Investors - Shrestha, Purna Man (Management Dynamics, 2020)
The study focuses on the factors influencing investment decisions of Nepalese investors in the stock market, with a sample size of 110 respondents of Surkhet Valley. The data are collected using structured questionnaire containing yes/no response questions, multiple choice questions, ranking questions, and Likert scale questions. The survey was conducted in June, 2018. The factors influencing investing decision are grouped into three main variables i. e. company related variable (CRV), risk and return related variable (RRV), and market related variable (MRV). In company related variable factors such as management team, financial performance, size, EPS, DPS are included, in risk return related variable expected return, past return, risk of the company, liquid securities etc. are included, and in market related variable factors such as market information, market price per share, dividend growths etc. are included. This study concluded that majority of investor prefer to by stock from primary market, investor analyze the company before making investment decision, investor monitor their portfolio occasionally, and most of the investor use own saving for making investment in stock. Finally, this study concluded that investment decision of Nepalese investor is more influenced by company related variable (CRV) than market related variable (MRV) and risk and return related variable (RRV). Positive and significant coefficient of company related variable (CRV) is observed in all regression models. It can, therefore, be concluded that the Nepalese investor makes investment decision observing the company related variable of Nepalese companies.